PENGARUH STRATEGI PEMBELAJARAN AKTIF TIPE LISTENING TEAM TERHADAP PEMAHAMAN KONSEP MATEMATIKA SISWA KELAS VIII MTsN DURIAN TARUNG PADANG TAHUN PELAJARAN 2012/2013 - Manda Sari, Sevya; Zulfaneti, Zulfaneti; Fitri, Dewi Yuliana (Pendidikan Matematika, 2013)
Â Â Â Â Â Â Â Â Â Â Â  The background of this research was lack of concept understanding of students couse study result of math of eight grade students of MTsN Durian Tarung Padang in the school year 2012/2013 are still low largely. This research aimed to determine whether studentsâ understanding of mathematical concepts by listening team type of active leaning strategy is better then the students understanding of math concepts with conventional. Type of this research is experimental, by design of random to the subject. The population in this study were eight grade students of MTsN Durian Tarung Padang in the school year 2012/2013. Technique of random sampling, was elected class ðð¼ð¼ð¼3 as an experimental class and class ðð¼ð¼ð¼4 as the control class. The instrument used was an essay test with reliability ððð=0.75. Based on the analysis test of studentsâ understanding of mathematics concepts for two class sample obtained experimental class average is 74.43 and control class is 62.45 with P-value = 0,004 is less than a = 0.05 this means that the ability of studentsâ understanding conceptâ of math by using listening team type active leaning strategy is better than study outcomes of math by using conventional learning at 95 % trusted level.